Hypersensitivity to Thromboxane A2 in Cholesterol-Rich Human Platelets - Tomizuka, Takuya; Yamamoto, Kyohei; Hirai, Aizan; Tamura, Yasushi; Yoshida, Sho (Thrombosis and Haemostasis, 1990)
The effect of changes in platelet membrane cholesterol content on thromboxane A2 (TXA2)-induced platelet activation was studied. Concentrations of 9,ll-epithio-ll,12-methano-TXA2 (STA2), a stable analogue of TXA2 which can cause half-maximal aggregation and release of [14C]serotonin in cholesterol-rich platelets were significantly lower than those in cholesterol-normal platelets. STA2-induced increase in cytosolic calcium concentration and [32P]phosphatidic acid formation in cholesterol-rich platelets were significantly greater than those in cholesterol-normal platelets. The maximal concentration of binding site (Bmax) for SQ29548 was significantly increased in cholesterol-rich platelets compared with cholesterol-normal platelets, while the equilibrium dissociation rate constant (Kd) for SQ29548 did not differ between cholesterol-rich and cholesterol-normal platelets. The present study suggested that sensitivity to TXA2 was increased by the incorporation of cholesterol into platelet membrane and that the cause of hypersensitivity to TXA2 in cholesterol-rich platelets may be partly explained by an increase in binding capacity for TXA2.